Gastric Neuroendocrine Neoplasm : WHO Classification 2019 - Eka Putra Pratama; Suly Auline Rusminan (Jurnal RSMH Palembang, 2020)
A B S T R A C TNeuroendocrine neoplasm (NEN) of gastric is a term that includes all tumour types withneuroendocrine differentiation of gastric, well differentiated or poorly differentiatedtumour. NEN is a new term in 2019 World Health Organization (WHO) classification ofdigestive system tumours. In WHO 2019 had many updates, one of them isneuroendocrine tumours (NET) grade 3 have been included in tumour category of welldifferentiated tumour or NET. Previously, NET G3 in WHO 2010 are included as poorlydifferentiated tumour or neuroendocrine carcinoma (NEC). This neoplasm is geneticallywell differentiated and because of that, WHO 2019 classification included them as a welldifferentiated tumour. For NEC, WHO 2019 subdivided them as NEC with small cells(SCNEC) and NEC with large cells (LCNEC). In WHO 2010, mixed type neuroendocrineneoplasms with other components of carcinoma are called mixed adenoneuroendocrinecarcinoma (MANEC). But, not all of non-neuroendocrine components areadenocarcinoma and it is possible that one of the components in not carcinoma. Becauseof that, in WHO 2019 the term has been changed to mixed neuroendocrine-nonneuroendocrine neoplasm (MiNEN).